Effect of the culture conditions over parameters of the action mode of Metarhizium anisopliae - VILLAMIZAR-R., LAURA FERNANDA; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2003)
The objective of the present work was to determine the effect of different culture conditions and potential virulence inductor substrates in the germination, adherence, and hydrophobicity of Metarhizium anisopliae conidia and its relationship with the biocontrol activity over Rhammatocerus schistocercoides. The fungus was cultured in Liquid and solid media, supplemented or not with the potential virulence inductors (colloidal chitin, homogenized of Locust wings and legs and wheat bran). TWo 1'1. anisopliae strains were evaluated, the isolate Mt004 which, in previous studies, demonstrated high activity against locust, and the isolate Mt006 which presented Iow biocontrol activity against this insect. Produced conidia were used in a bioassay and in all cases the highest biocontrol activity was obtained with the strain Mt004. Evaluated substrates produced an effect over measured parameters with both strains however, the highest mortality was obtained with conidia produced in liquid culture media supplemented with homogenized of locust wings and legs and wheat bran, suggesting that these substrates had a virulence inductor effect, considering that germination, adherence, and hydrophobicity of these conidia were also increased. The results indicate that the fungus culture medium determines the characteristics of the produced biomass, which could be related to its virulence.